Twitter Sebagai Sarana Mengakses Informasi Pelecehan Seksual (Studi Netnografi Thread Korban Pelecehan “Fetish Kain Bungkus”) - Rachel Anastasya; Dedi Sahputra; Ressi Dwiana (Universitas Medan Area, 2022)
This research entitled Social Media Twitter as a Means to Access Information of Sexual Harassment (Netnography Study of Harassment Victim’s Thread